Self-Reported Prevalence of HIV Testing Among Those Reporting Having Been Diagnosed With Selected STIs or HCV, United States, 2005–2016. (May 2020) - Patel, Shilpa N.; Delaney, Kevin P.; Pitasi, Marc A.; Oraka, Emeka; Tao, Guoyu; Van Handel, Michelle; Kilmer, Greta; DiNenno, Elizabeth A.
Abstract : Background: Persons with STIs or HCV infection often have indicators of HIV risk. We used weighted data from 6 cycles of the National Health and Nutrition Examination Survey (NHANES) to assess the proportion of persons who reported ever being diagnosed as having a selected STI or HCV infection and who reported that they were ever tested for HIV. Methods: Persons aged 20 to 59 years with prior knowledge of HCV infection before receiving NHANES HCV RNA–positive results (2005–2012) or reporting ever being told by a doctor that they had HCV infection (2013–2016), or ever had genital herpes, or had chlamydia or gonorrhea in the past 12 months were categorized as having had a selected STI or HCV infection. Weighted proportions and 95% confidence intervals were estimated for reporting ever being tested for HIV for those who did and did not report a selected STI or HCV infection. Results: A total of 19, 102 respondents had nonmissing data for STI and HCV diagnoses and HIV testing history; 44.4% reported ever having been tested for HIV, and 5.2% reported being diagnosed as having a selected STI or HCV infection. The proportion reporting an HIV test was higher for the group that reported an STI or HCV infection than for the group that did not. Conclusion: Self-reported HIV testing remains low in the United States, even among those who reported a previous selected STI or HCV infection. Ensuring HIV tests are conducted routinely for those with overlapping risk factors can help facilitate the diagnosis of HIV infections. Abstract : An analysis of the National Health and Nutrition Examination Survey data found that HIV testing remains low in the United States, even among those who reported a previous diagnosis of selected STIs or HCV infection.